2000
DOI: 10.1037/0278-6133.19.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Job strain and risk indicators for cardiovascular disease in young female nurses.

Abstract: Pickering, 1998). However, studies of women more often fail to find a job-strain effect on BP than studies of men, which Schnall et al. (1994) attributed to the lower prevalence of hypertension at the employable age in women. Social support has been found to be associated with lower BP in the majority of srudies (Uchino et al., 1996), but the effects seem to apply only to social support received from farnily and friends rather than job-related social support.Studies on male or combined male and female popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 92 publications
4
31
0
Order By: Relevance
“…29,30 It has been suggested that perceived job stress may be related to elevated plasma fibrinogen, although results are not consistent. 25,[31][32][33][34][35][36][37] In general, the dimension of job control has been more consistently related to fibrinogen concentrations than job demands, which is in line with our findings. 35,38 -40 Fewer studies have been conducted on possible associations between job stress and concentrations of CRP and SAA.…”
Section: Discussionsupporting
confidence: 92%
“…29,30 It has been suggested that perceived job stress may be related to elevated plasma fibrinogen, although results are not consistent. 25,[31][32][33][34][35][36][37] In general, the dimension of job control has been more consistently related to fibrinogen concentrations than job demands, which is in line with our findings. 35,38 -40 Fewer studies have been conducted on possible associations between job stress and concentrations of CRP and SAA.…”
Section: Discussionsupporting
confidence: 92%
“…Number of studies reporting a statistically significant deleterious effect / total number of studies having these methodological characteristics (reference number) reporting a deleterious effect of job strain on blood pressure (BP) according to gender, study designs (crosssectional, prospective or case-control), BP measurements (office or ambulatory) and outcome (hypertension or BP level). (131,134,135,149,157,177) 0 / 0 0 / 1 (142) 0 /0 0 / 7 BP level 1 (138) / 7 (129,138,152,171,178,193,214) 1 (150 ) / 3 (126,150,156) 1 (180) / 3 (142,161,180) 1 (166) / 1 (166) 4 / 14…”
Section: Studies On Eri Modelmentioning
confidence: 99%
“…Life-style risk factors, and standard cardiovascular studies background variables must obviously be also included in this study design (see for example listing of often measured variables in Kristensen; Riese; Theorell et al) [21][22][23]. However, since many of these measures are well identified in the existing literature, in this paper we will focus discussion on less discussed measurement problems related to detection of "physiological exhaustion".…”
Section: R E V I E W P a P E R S R Karasek Et Al Ijomeh 2010;23(3) 304mentioning
confidence: 99%
“…The typical presented list of risk factors for CVD (or MD or MSD) is long, with factors at many levels -physiological and social [21][22][23]. We can summarize our suspicions about why the progress has been so slow via the following critique of the existing literature that addresses the combination of questions relating to "work-stress-disease."…”
Section: Section II Addressing the Limitations In Our Current Researchmentioning
confidence: 99%
See 1 more Smart Citation